2000
DOI: 10.1046/j.1365-2648.2000.01491.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing postpartum pain: a review of research pertaining to perineal care in childbearing women

Abstract: This paper provides a review of literature that relates to perineal pain and care. Articles evaluated include systematic reviews and research papers from the disciplines of midwifery, physiotherapy and obstetrics. The major themes to emerge from the literature and be reviewed are the need for episiotomy, suturing methods and materials, assessment of perineal trauma, treatment of perineum in the postpartum period, and postpartum recovery. Research has highlighted that many practices relating to perineal care re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
8
0
2
Order By: Relevance
“…Recently, several investigators have studied ways to reduce the pain during episiotomy repair, such as previous care before the intrapartum period, different ways to suture or by special care during the postpartum period (11–14). No previous study has assessed the effect of SSC on maternal pain during episotomy repair.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several investigators have studied ways to reduce the pain during episiotomy repair, such as previous care before the intrapartum period, different ways to suture or by special care during the postpartum period (11–14). No previous study has assessed the effect of SSC on maternal pain during episotomy repair.…”
Section: Introductionmentioning
confidence: 99%
“…Three systematic reviews have demonstrated that a subcuticular continuous suture of polyglycolic acid will heal better and be associated with less short term pain than other methods 7–9 . However, it has been cautioned 10 that research needs to be conducted into the long term outcomes of such recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Promotion of optimal healing after childbirth through nutrition and perineal hygiene has been an area of routine care in nursing and midwifery. Although a variety of solutions, including herbal therapies, and techniques have been used and suggested, perineal care continues to be an area in need of clinical research (19‐21). Prevention of labial or clitoral adhesions may be possible through personal hygiene techniques of instructing women to manually gently separate the labia several times a day while urinating, which may also be a consequence of use of a peri‐bottle or sitz bath.…”
Section: Discussionmentioning
confidence: 99%